Pengaruh Harga, Kualitas Makanan dan Suasana Terhadap Kepuasan Pelanggan Pada Rumah Makan Kindai Masakan Banjar di Malang - Yulinda Putri Melinia; Muhammad Agus Salim; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThe purpose of this study was to determine how the effect of Price, Food Quality and Atmosphere on Customer Satisfaction at the Kindai Cuisine Banjar Restaurant in Malang. The population in this study consisted of customers of Kindai Restaurant in Malang. Data collection techniques in this study using a questionnaire. The questionnaire in this study is a questionnaire that uses a Likert scale, to clarify the variables being measured. The data collection method in this study used a purposive sampling technique by distributing questionnaires to respondents who were determined by the criteria, namely customers who had made purchases at least 2 times at Kindai Restaurant. The results of the study partially show that: 1) There is an effect of price on customer satisfaction at the Kindai Cuisine Banjar Restaurant in Malang. 2) The influence of food quality on customer satisfaction at Kindai Restaurant Banjar cuisine in Malang. 3) There is an influence of Atmosphere on Customer Satisfaction at the Banjar Cuisine Kindai Restaurant in Malang. Keywords: Price, Food Quality, Atmosphere and Customer Satisfaction.